Non-thyroid cancer in Northern Ukraine in the post-Chernobyl period: Short report. Issue 3 (June 2015) - Hatch, M.; Ostroumova, E.; Brenner, A.; Federenko, Z.; Gorokh, Y.; Zvinchuk, O.; Shpak, V.; Tereschenko, V.; Tronko, M.; Mabuchi, K.
Highlights: First systematic report on non-thyroid cancer incidence post-Chernobyl in Ukraine. Well-defined cohort exposed at radiosensitive ages. Cancers ascertained through linkage with high-quality Registry. No significant increase to date in estimated SIRs. Trends for leukemia warrant continued follow-up. Abstract: The Chernobyl nuclear power plant accident in Ukraine in 1986 led to widespread radioactive releases into the environment – primarily of radioiodines and cesium – heavily affecting the northern portions of the country, with settlement-averaged thyroid doses estimated to range from 10 mGy to more than 10 Gy. The increased risk of thyroid cancer among exposed children and adolescents is well established but the impact of radioactive contamination on the risk of other types of cancer is much less certain. To provide data on a public health issue of major importance, we have analyzed the incidence of non-thyroid cancers during the post-Chernobyl period in a well-defined cohort of 13, 203 individuals who were <18 years of age at the time of the accident. The report is based on standardized incidence ratio (SIR) analysis of 43 non-thyroid cancers identified through linkage with the National Cancer Registry of Ukraine for the period 1998 through 2009. We compared the observed and expected number of cases in three cancer groupings: all solid cancers excluding thyroid, leukemia, and lymphoma. Our analyses found no evidence of a statistically significant elevation in cancer risks in this cohort exposed at radiosensitive ages, although the cancer trends, particularly for leukemia (SIR = 1.92, 95% confidence interval: 0.69; 4.13), should continue to be monitored.